The GATE-RTion/IDEAL Independent Dose Calculation System for Light Ion Beam Therapy - Grevillot, L.; Boersma, D. J.; Fuchs, H.; Bolsa-Ferruz, M.; Scheuchenpflug, L.; Georg, D.; Kronreif, G.; Stock, M. (Frontiers in Physics, 2021)
Patient specific quality assurance can be improved using an independent dose calculation system. In addition, the implementation of such a system may support light ion beam therapy facilities in reducing the needs for beam time, by substituting some of the experimental patient-specific quality assurance procedures by independent dose calculation. The GATE-RTion-based IDEAL system for light ion beam therapy was developed for this purpose. It was built in a DICOM-in, DICOM-out fashion, for easy integration into a state-of-the-art technology-based workflow for scanned ion beam therapy. This article describes the IDEAL system, followed by its clinical implementation at MedAustron for proton and carbon ion beams. Medical physics acceptance and commissioning steps are presented together with key results. Finally, five clinical cases are described, i.e. two proton and three carbon ion treatments. Dosimetric benchmarking against TPS calculations are presented and discussed in details. The IDEAL system was found to satisfy the clinical requirements for independent dose calculation of scanned ion beam delivery systems and is being clinically implemented at MedAustron. The open-source code as well as the documentation was released on the OpenGATE collaboration website, thus allowing for long term maintenance and future upgrades based on a more widespread utilization.